Relationship of academic performance of students in first year of university in Chile and entry instruments for their selection - Vergara-Díaz, Gaston (2017)
Several studies have been carried outundertaken in relation to the academic performance of freshman students enrolled in Universities from Chile. However, few studies have focused on the relationships between the entrance selection instruments applied and their academic performance at the university. A sample of 440 students of commercial engineering belonging to five different promotions from the Universidad Austral de Chile was selected to study the instruments used for admission to this career. The instruments evaluated were the university selection test (PSU) and grade average of high school showed by the students in relation to the grade point average (GPA) of the first year at the University. The grade average of high school explains better the academic performance of the students in comparison to the PSU, showing a higher correlation for the first and second academic semester.